Microbial profile and antimicrobial properties of edible bird nest - Zuber, Shazreena (2018)
Edible-birdnest (EBN) is the hardened salivary secretion of swiftlets (Aerodramus sp.) that has been reported to have numerous nutritional benefits. The consumption and trade of EBN can be traced as far back since the Tang dynasty and considered to be one of the expensive animal by-product consumed by humans. In recent years, various scientific studies have been carried out to explain the medicinal properties of EBN. However, there is a limited study on the microbiological diversity of EBN and the antimicrobial properties of EBN. In this study, the microbial quality of 45 EBN comprising of raw unclean and raw clean EBN from two different premises were analyzed, namely premise A (GMP-certified premise) and premise B (non GMP-certified premise). Dilution of EBN samples were made and microbial enumeration was done using 3M™ Petrifilm. The results revealed that the Total Aerobic Count (TAC) of raw clean EBN in both premises and Total Coliform Count (TCC) in all EBN in premise B except for 8 weeks old EBN exceeded limit stated in Malaysia Standard (MS 2334:2011; SIRIM/DVS 3:2015). A total of 255 bacteria and 201 fungi species were isolated from EBN and identified using biochemical test and API kit, the most common bacteria encountered in both premises were Staphylococcus sp., Corynebacterium sp. and Actinomyces sp. While in premise B, Aeromonas sp. and Ochrobactrum anthropi were also found to be prevalent. The difference in occurrence of bacteria in EBNs in both premises at all stages were found to be non-significant (P<0.05). As for fungi, Fonsecaea pedrosoi were the most encountered fungi in premise A. While in premise B, Penicillin sp. and Candida sp. were the most frequently isolated in that premise. The most common fungi encountered in both premises were Aspergillus niger and Mucor sp. Differences in occurrence of the fungi were only significant in the raw unclean EBN and non-significant in the rest of the stages. The bacteria and fungi mostly found in this study were environmental microorganism. It could be concluded that although one of the premise practices Good Manufacturing Practice (GMP), however the results indicates that the cleaning process of both premises are similar. The source of contamination could be caused by mishandling, cleaning, processing step and equipment. Another study was carried out to compare the prevalence of bacteria from 30 swiftlet faeces in bird ranch located at three different geographical areas (oil palm area, paddy field area, town area). A total of 174 bacteria species were isolated and identified with the most encountered bacteria from the paddy field area were Escherichia coli (35.7%), followed by Proteus sp. and Vibrio sp. (17.8%). While in the town area, E. coli (20%) and Proteus mirabilis (10%) were the most frequently isolated bacteria, and in oil palm plantation, the most common bacteria were Enterobacter cloacae (17%) and Serratia marcescens (13%). As for Gram-positive bacteria, Staphylococcus sp. (70%), Streptococcus sp. (42.8%), and Actinomyces sp. (50%) were found to be most common bacteria in faeces from oil palm plantation, paddy field and town area respectively. The prevalence of bacteria in all three locations were found to be non-significant (P<0.05). In conclusion, the similarity in prevalence of bacteria in faeces in all three areas were because the isolates were part of normal faecal and environmental flora and relatively similar eating habits of the swiftlets which is dependent on two main insect orders, Diptera and Hymenoptera that were mainly found in the edible-nest swiftlets in various locations around Malaysia. The therapeutic qualities of EBN were also screened, and in this study the antibacterial and antifungal activity of 15 pure EBN extracts were screened using the disk and agar well diffusion methods. Despite many reports confirming EBN possessed bioactive component, unfortunately, all 15 pure EBN extract tested showed no inhibitory effects against selected bacteria which included Staphylococcus aureus, Enterococcus faecalis, Bacillus cereus, Rhodococcus equi, E. coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella typhimurium and Pasteurella multocida. Following that, no antifungal activity was observed against fungal strains A. niger, Aspergillus flavus, Malasezzia sp., Candida albicans and Mucor sp. The absence of antimicrobial activity could be caused by the loss of the bioactive component responsible for the antimicrobial properties in EBN possibly due to the cleaning, drying, extraction process and long period of EBN storage.